1997
DOI: 10.1093/gerona/52a.2.m68
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Levels and Stress Reactivity in Human Aging

Abstract: Results indicate moderate increases in basal cortisol levels, but do not support the hypothesis that cortisol responses to a stressor increase in magnitude or duration during normal human aging. Gender differences in stress reactivity warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 44 publications
10
66
1
2
Order By: Relevance
“…Specifically, advancing age in adult humans is associated with increases in total body fat and abdominal adiposity, as well as a progressive shift from a peripheral to a central/abdominal fat pattern (6,7). Consistent with this, many if not all of the putative adiposity-sensitive physiological signals described above increase with age (32,33). Thus changes in one or more of these signals could account for the apparent important contribution of increased abdominal-to-peripheral fat distribution to age-associated changes in autonomic-circulatory function.…”
Section: Ans-circulatory Function Adiposity and Agingmentioning
confidence: 59%
“…Specifically, advancing age in adult humans is associated with increases in total body fat and abdominal adiposity, as well as a progressive shift from a peripheral to a central/abdominal fat pattern (6,7). Consistent with this, many if not all of the putative adiposity-sensitive physiological signals described above increase with age (32,33). Thus changes in one or more of these signals could account for the apparent important contribution of increased abdominal-to-peripheral fat distribution to age-associated changes in autonomic-circulatory function.…”
Section: Ans-circulatory Function Adiposity and Agingmentioning
confidence: 59%
“…Until recently, it has not been clear whether similar changes occur in the human HPA axis during aging. Several groups have reported age-associated increases in resting cortisol levels, especially near the nadir of the cortisol circadian rhythm (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The magnitude of pituitary-adrenal responses to ovine corticotropin-releasing factor (CRF) has generally not been found to change with aging in humans (17,18).…”
Section: A Ging In Rodents Has Been Found To Results In Pro-mentioning
confidence: 99%
“…With decreasing ability to maintain negative feedback, diurnal rhythms are expected to become altered. Nicolson, Storms, Ponds, & Sulon (1997) found a moderate increase in basal salivary cortisol levels with age but a diminished reactivity with age. In a longitudinal study, Lupien, Lecours, Schwartz, Sharma, Hauger, Meaney, & Nair (1996) found no age-associated change in basal plasma cortisol levels.…”
Section: Introductionmentioning
confidence: 86%